The Effect of Problem-Based Learning Model Assisted by Puzzle Media on Elementary Students' Mathematical Problem-Solving Ability - Yosha Sheptia; Hafiziani Eka Putri; Alfiana Nurussama (Universitas Wiralodra, 2026)
The purpose of this study is to examine how students’ ability to solve mathematical problems is influenced by problem-based learning (PBL) using puzzles as a teaching tool. This study adopted a quasi-experimental method using a quantitative approach with a non-equivalent control group design. A total of 48 participants were selected as the sample through purposive sampling because the selected classes had similar academic characteristics and met the criteria required for the quasi-experimental design. The assessment consisted of a written report and five essay-type questions. The experimental group obtained a mean score of 69.58, while the control group obtained a mean score of 54.04. The independent sample t-test showed a significant difference between the two groups, p-value < 0.001, with a large effect size ( Cohen’s d = 2.370), indicating that the Problem-Based Learning (PBL) model assisted by puzzle media had a strong positive impact on students’ mathematical problem-solving abilities. Regression analysis revealed a coefficient of determination of 52.5% and a correlation coefficient of 0.700. The findings from the regression analysis confirm that the puzzle-based learning method has a significant impact, contributing more than fifty percent to the improvement of students' ability to solve mathematical problems. Thus, the main conclusion indicates that students' ability to handle numerical problems is significantly influenced and positively driven by the puzzle-assisted problem-based learning model.